Plot of Transition in Novel by F. Kafka “Metamorphosis” - O. N. Turysheva (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article puts forward the hypothesis that in the novel by F. Kafka “Metamorphosis” a mythological plot of the transition is realized. The author interprets this type of plot as an event when a hero crosses the border between life and death. The mythocritical and immanent methodology is used. It is concluded that in the Kafka’s novel the plot of the transition is reproduced in a reduced version. The significance of this reduction is proved: its discovery allows revealing the deep foundations of the tragic content of the novel. The author analyzes the approaches existing in science in interpreting the image of the three tenants who settled in Mr. Zamza’s apartment after the hero’s transformation. In a polemical perspective, some interpretations of the image of guests are considered. A new interpretation of this collective character is put forward: it is raised to the figure of a psycho-pump in the article. It is shown that the tragic pathos of the novel is associated with the event of the expulsion of the tenants, which is interpreted as a reduction of the rite of transformation. It is proved that the function of the image of tenants is to strengthen the semantics of family betrayal. Observations are made on the nature of Kafka's mythologism based on the material of its mythological miniatures.